2020
DOI: 10.1101/2020.09.01.20178848
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mental healthcare and service user impact of the COVID-19 pandemic: results of a UK survey of staff working with people with intellectual disability and developmental disorders

Abstract: Background Very little is known about the impact of previous epidemics on the care of people with intellectual and developmental disabilities, particularly in terms of mental health services. The COVID-19 pandemic has the potential to exacerbate existing health inequalities as well as expose gaps in service provision for this vulnerable population group. Methods We investigated the responses of 648 staff working in mental healthcare with people with intellectual disabilities and/or developmental disabilities.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…(107). Telemental health may also be less suitable for treating trauma (63, 103), for clients with severe anxiety (63), learning difficulties or autism (106), children (63), and clients with cognitive impairment (63, 91).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(107). Telemental health may also be less suitable for treating trauma (63, 103), for clients with severe anxiety (63), learning difficulties or autism (106), children (63), and clients with cognitive impairment (63, 91).…”
Section: Resultsmentioning
confidence: 99%
“…Improved communication was noted between staff when using telemental health when compared to traditional face-to-face care, as the use of online file sharing or discussion platforms facilitated communication between staff e.g. (75, 106). The use of online methods also facilitated staff training and some staff reported that remote working resulted in a better work-life balance e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Despite these aforesaid studies, video conferencing remains an underdeveloped opportunity vis-a-vis providing mental health support to people with intellectual disabilities (e.g. Rose et al 2020, Sheenan et al 2020.…”
Section: Discussionmentioning
confidence: 99%
“…In their commentary, Courtenay and Perera (2020) stated the pandemic can be an enormous challenge for intellectual disability staff who must protect themselves and individuals with intellectual disabilities from infection while caring for those who are infected. Intellectual disability staff may need to take special care for individuals with intellectual disabilities who do not understand the need for preventive measures or exhibit behavioral changes in response to preventive measures and disrupted routines ( Courtenay & Perera, 2020 ; Schuengel et al., 2020 ; Sheehan et al, 2020 ; Tromans et al, 2020 ). A UK study found that implementing public health measures such as self-isolation, hand washing, and physical distancing with individuals with intellectual disabilities is extremely difficult for intellectual disability staff ( Sheehan et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%